A note on two fundamental recursive sequences - Farhadian, Reza; Jakimczuk, Rafael (Annales Mathematicae Silesianae, 2021)
In this note, we establish some general results for two fundamental recursive sequences that are the basis of many well-known recursive sequences, as the Fibonacci sequence, Lucas sequence, Pell sequence, Pell-Lucas sequence, etc. We establish some general limit formulas, where the product of the first n terms of these sequences appears. Furthermore, we prove some general limits that connect these sequences to the number e (≈2:71828...).